2002
DOI: 10.1016/s0092-8674(02)00734-1
|View full text |Cite
|
Sign up to set email alerts
|

A Senescence Program Controlled by p53 and p16INK4a Contributes to the Outcome of Cancer Therapy

Abstract: p53 and INK4a/ARF mutations promote tumorigenesis and drug resistance, in part, by disabling apoptosis. We show that primary murine lymphomas also respond to chemotherapy by engaging a senescence program controlled by p53 and p16(INK4a). Hence, tumors with p53 or INK4a/ARF mutations-but not those lacking ARF alone-respond poorly to cyclophosphamide therapy in vivo. Moreover, tumors harboring a Bcl2-mediated apoptotic block undergo a drug-induced cytostasis involving the accumulation of p53, p16(INK4a), and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
830
2
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 965 publications
(882 citation statements)
references
References 36 publications
27
830
2
11
Order By: Relevance
“…Growing evidence indicate that some tumor cells treated with chemotherapeutic drugs could escape apoptosis by developing cell-cycle arrest leading to senescence [40,41]. We hypothesize that TRAIL is capable to induce senescence that could help tumor cells to escape apoptosis.…”
Section: Trail Induced Senescence-like Phenotype (Slp) Of Tumor Cellsmentioning
confidence: 87%
“…Growing evidence indicate that some tumor cells treated with chemotherapeutic drugs could escape apoptosis by developing cell-cycle arrest leading to senescence [40,41]. We hypothesize that TRAIL is capable to induce senescence that could help tumor cells to escape apoptosis.…”
Section: Trail Induced Senescence-like Phenotype (Slp) Of Tumor Cellsmentioning
confidence: 87%
“…Targeting DDR pathways to improve cancer treatment F Al-Ejeh et al a wild-type p53 or p16 model of Burkitt's lymphoma revealed that responses to cyclophosphamide correlated with increases in the senescence-associated marker bgalactosidase (SA-b-gal) that is lost when p53 or p16 mutations were introduced (Schmitt et al, 2002). Tissuespecific increases of SA-b-gal were associated with low p53 staining and high p16 staining in patients receiving induction chemotherapy for breast cancer (te Poele et al, 2002).…”
Section: Clinical Relevance Of Cell Death Pathwaysmentioning
confidence: 99%
“…Recent studies demonstrated that the ARF tumor suppressor inhibits cell cycle through p53-dependent and p53-independent mechanisms. [38][39][40][41][42][43] Moreover, ARF/p53 double-null B cells are more resistant to Myc-induced apoptosis than cells lacking ARF or p53 alone. 31 At face value, these results imply that the p53-independent ARF function might be selected against in MIF-KO Em-Myc B-lymphomas.…”
Section: Mif-deficient Lymphomas Contain P53 Inactivating Mutations Amentioning
confidence: 99%